2013
DOI: 10.1111/eci.12048
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin β4 protects C57BL/6 mice from bleomycin‐induced damage in the lung

Abstract: This is the first report that shows a Tβ4 protective role in lung toxicity associated with BLEO in a mouse model. Future studies are needed to assess its putative antifibrotic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 19 publications
2
29
1
Order By: Relevance
“…In contrast to the protective result of Tb4 on the early fibrosis at 7 days after bleomycin instillation as previously described [4,5], treatment with Tb4 failed to protect bleomycin-treated mice from lung fibrosis observed at 14 and 21 days. As shown in Figure 1, the histological features of the Sham and Sham + Tb4 mice lungs are identical.…”
Section: Effects Of Tb4 On Bleomycin-induced Lung Fibrosis In Cd-1 Micecontrasting
confidence: 69%
See 2 more Smart Citations
“…In contrast to the protective result of Tb4 on the early fibrosis at 7 days after bleomycin instillation as previously described [4,5], treatment with Tb4 failed to protect bleomycin-treated mice from lung fibrosis observed at 14 and 21 days. As shown in Figure 1, the histological features of the Sham and Sham + Tb4 mice lungs are identical.…”
Section: Effects Of Tb4 On Bleomycin-induced Lung Fibrosis In Cd-1 Micecontrasting
confidence: 69%
“…Accordingly, our recent in vivo studies demonstrated wide protective effects of Tb4 in mice treated with bleomycin, and in particular significant inhibitory results on bleomycin-induced inflammation and on early fibrosis at 7 days [4,5]. By using the same dose, route and scheduling of previous researches, in this current study we addressed the potential role of Tb4 in halting progression of fibrosis.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Thymosinb4 can also bind to stabilin-2, a membrane receptor involved in the engulfment of apoptotic cells [4]. The ability of thymosin-b4 to regulate cell movement and turnover has led to studies showing that it can stimulate coronary vasculogenesis and angiogenesis [5] and regulate inflammation and fibrosis in mouse models of lung, heart and cornea injury [6][7][8]. Thymosin-b4 derivatives have similar properties.…”
Section: Introductionmentioning
confidence: 99%
“…A peptide derived from its aminoterminal end, Ac-sdkp, is responsible for the antifibrotic effects of angiotensin converting enzyme inhibitors(42). Conte et al (43) found that exogenous Tβ4 is protective in mice receiving intratracheal bleomycin. In a subsequent paper, they attribute these findings to Tβ4-mediated reduction in the numbers of IL-17 producing cells in circulation as well as decreased IL-17 levels in the lung tissue(44).…”
Section: Pathogenesismentioning
confidence: 99%